How Firm Size Moderates the Impact of Intellectual Capital, CSR, and Capital Structure on Financial Performance? - Mar Atul Jamilah; Kholilah Kholilah; Nungki Kartikasari (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Purpose: This study aims to examine the effect of intellectual capital, CSR, and capital structure on financial performance, as well as to examine the role of company size as a moderating variable in financial sector companies in Indonesia. Method: This study uses a quantitative approach with panel data regression analysis and Moderated Regression Analysis (MRA) techniques using EViews software. The sample consists of 53 financial sector companies listed on the Indonesia Stock Exchange in 2021–2023 with a total of 159 observations. Results: The results show that intellectual capital has a positive and significant effect on financial performance. Conversely, CSR and capital structure do not have a significant effect on financial performance. In addition, company size has been shown to moderate the effect of intellectual capital on financial performance, but does not moderate the relationship between CSR and capital structure on financial performance. Implications: The findings of this study have practical implications for financial sector companies to prioritise the management of intellectual capital as a strategic asset in improving financial performance. In addition, the results of this study also contribute academically to enriching the literature on internal factors that influence the financial performance of financial sector companies. Novelty: The novelty of this study lies in the use of the latest data from Indonesian financial sector companies for the period 2021–2023 and the testing of company size as a moderating variable in an empirical model, which is still relatively rarely studied in the context of the financial sector.